Elderly falls, multifactorial medical problem - how to assess the risk? - Jankowska, Paula; Jankowski, Krzysztof; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
IntroductionAdvanced age of a large part of society is associated with many health as well as social and economic consequences. Among them, disorders of mobility and falls of elderly have important place. The pathophysiology of falls among elderly is complex. It includes visual impairment, vestibular disorders, dementia, sarcopenia and use of many drugs. Screening for falls risk is essential part of everyday primary healthcare provider practice. Critical review of medications, management of chronic diseases may prevent falls. Apart from this, there are some professional functional assessment instruments available.ObjectiveThe objective of this work is to present reasons of elderly falls and functional assessment instruments suitable to assess risk of falls.ResultsAmong analyzed instruments Timed Up-and-Go test, Elderly Fall Screening Test, Tinetti Performance Oriented Mobility and Berg Balance Test were chosen to be described, due to the best characteristics according to needs of primary care.ConclusionFalls are important health problem in elderly. Frequently, falls result in serious injury and following disability. Consequences of elderly falls may be even fatal. Thus, healthcare providers should pay attention especially to modifiable risk factors of falls. Among them is polypharmacy and use of selected drug groups. The burden of coordination of patient treatment, critical review of administered drugs and systematic screening for increased falls risk lays on family doctors. The most suitable for primary healthcare setting instrument designed to address this aim, seems to Timed Up-and-Go test. Tools as Elderly Fall Screening Test, Tinetti Performance Oriented Mobility and Berg Balance Test can be used as well.